2009
DOI: 10.1080/00343400802154573
|View full text |Cite
|
Sign up to set email alerts
|

Production of University Technological Knowledge in European Regions: Evidence from Patent Data

Abstract: Acosta M., Coronado D., Leon M. D. and Martinez M. A. Production of university technological knowledge in European regions: evidence from patent data, Regional Studies. This paper explores the European regional distribution of the production of new technological knowledge generated by universities, as measured by patent counts. The empirical basis for this study is a unique panel data set of 4580 European university patents from 1998 to 2004. The main findings were a strong regional and sectoral concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…For the rest of the variables, the results show, as expected, a positive relation between the funding of R&D and the number of patents, as in other empirical analyses (Coupé, 2003;Payne and Siow, 2003;Azagra et al, 2006;Acosta et al, 2008). The results of the estimations show the convenience of splitting the funded R&D between the two sources of funding, income for basic research and contractual funding for applied research.…”
Section: Tables 2 and 3 Results Of Estimationssupporting
confidence: 68%
See 1 more Smart Citation
“…For the rest of the variables, the results show, as expected, a positive relation between the funding of R&D and the number of patents, as in other empirical analyses (Coupé, 2003;Payne and Siow, 2003;Azagra et al, 2006;Acosta et al, 2008). The results of the estimations show the convenience of splitting the funded R&D between the two sources of funding, income for basic research and contractual funding for applied research.…”
Section: Tables 2 and 3 Results Of Estimationssupporting
confidence: 68%
“…Therefore expenditures on R&D have been used in the majority of applied studies of the determinants of academic patents (Coupé, 2003;Payne and Siow, 2003;Azagra et al, 2006;Acosta et al, 2008). In particular, Coupé (2003) examines the relation between expenditure on R&D and academic patents in detail and confirms that it is a significant variable.…”
Section: Model Specification and Datamentioning
confidence: 99%
“…Furthermore, up to 70% of the US academic R&D is sponsored by US government agencies (National Science Board, 2012), rendering thus academic R&D an interesting policy related instrument. Most importantly, studies have shown that academic research has significant positive effects in regional industry R&D and economic growth (Jaffe, 1989;Acosta et al, 2009 Following the literature, we express the inputs in both production processes as follows:…”
Section: Stochastic Frontier Model Of Productionmentioning
confidence: 99%
“…However, the Spanish case may be peculiar due to the small average size of the country's universities. For the EU-15, still at regional level, returns to R&D expenditure appear to be constant in the period 1998 to 2002 (Acosta et al 2008). To what extent these results apply at country level, for the EU-27, and over a longer time span is unknown; given the slightly more abundant microeconomic evidence, we expect low returns to R&D expenditure when using countries as the unit of observation.…”
Section: Differences Between the Determinants Of University And Pro Pmentioning
confidence: 84%
“…In many of the microeconomic production functions estimated using universities as the unit of observation (Coupé 2003;Azagra et al 2003;2006a, b;Baldini et al 2006;Carayol 2007;Acosta et al 2008;Wong and Singh 2009;Baldini 2009), one of the theoretical determinants of university-owned patents is university R&D expenditures and/or other measures for university research size, such as R&D staff. The impact of R&D on patents tends to be positive and significant, with elasticities lower than 1.…”
Section: Differences Between the Determinants Of University And Pro Pmentioning
confidence: 99%